Religieuze tolerantie op haar retour? Hete discussies, kalme reacties en bedenkelijke effecten - Vellenga, Sipco (Religie & Samenleving, 2012)
This article analyses the responses to and societal effects of increasing pressure on orthodox religious groups in the public and political debate in the Netherlands. The response to religious criticism by orthodox groups is not necessarily aggressive as research on the way Muslim organizations reacted to the anti-Islam film Fitna (2008) shows. Their calm response can be attributed to the way they framed this film and the support they experienced from the Dutch government. When the pressure on orthodox religious groups will increase, it is likely they will feel threatened. This feeling can contribute to radicalization or segregation. On a societal level restrictions on religion can contribute to for instance the judicial emancipation of women and homosexuals within orthodox religious groups, but at the same time stimulate processes of exclusion and societal polarization. With reference to the relative weak power position of orthodox religious groups in Dutch society, the author suggests an open and (more) relaxed approach to these groups.